Development and application of simulation experimental system for impact dynamic effect and disaster-causing characteristics of coal and gas outburst - Xuelin YANG; Guangcai WEN; Haitao SUN; Jie CAO; Bo WANG; Linchao DAI; Jun LU (Meitan xuebao, 2023)
As the disaster-causing characteristics of coal and gas outburst and the mechanism of induced mine airflow disaster are not clear, the facilities such as air door and self-rescue system are often arranged on site according to miner’s experience, thus it is difficult to take safety protection measures and formulate scientific and reasonable emergency plan. In order to accurately grasp the impact dynamic effect and disaster-causing characteristics of coal and gas outburst, based on the similarity theory, a set of physical simulation experimental system considering the disaster-causing strengthening effect caused by gas in the pressure relief area around the outburst hole was developed. And the key parameters of the gas supplement device were determined through strict calculation based on the outburst model and gas seepage theory. The experimental system mainly includes outburst hole dynamic system, outburst excitation device, roadway simulation system and data acquisition and control center, which can simulate outburst dynamic phenomena such as the formation and propagation of outburst shock wave, the migration of outburst coal-gas two-phase flow and gas countercurrent in the simulated roadway. The simulation experiment of outburst disaster with a gas pressure of 0.8 MPa was carried out. And the forming process of outburst shock wave was directly observed with a high-speed camera. The results show that the outburst shock wave is formed instantly in the pipeline at the moment of outburst, followed by impact flow, outburst gas flow and coal-gas two-phase flow. The comparable velocities of each parameter are in the order: the air shock wave velocity > impact flow velocity > outburst gas-flow velocity > outburst coal-gas two-phase flow front velocity. The maximum velocities of each parameter are 546.5, 496.7, 112.6 and 51.5 m/s respectively, and gradually decay along the pipeline. At the moment of outburst, high-pressure gas poured into the roadway space from the outburst hole, resulting in gas reflux. During the outburst process, the gas pressure inside the outburst hole decreases exponentially. After the outburst occurs, the gas concentration in the roadway changes with time in “sudden rise stage” and “slow decline stage”, and the migration mode of the gas outburst in the roadway mainly includes “displacement" and “diffusion”. The accumulation height and quality of outburst coal along the main roadway are consistent. The difference of grain size distribution between outburst coal and raw coal is mainly concentrated in 0−500 μm, while the difference of maximum grain size distribution is mainly concentrated in 150−200 μm. In addition, the proportion of coal powder with particle size distribution in the range of 150−200 μm increases with the increase of the distance from the outburst mouth, showing a strong sorting ability.